The Influence of STEM-PBL to Improve Students' Critical Thinking Skills in Straight Line Kinematics Material - Harianty, Andi Putri; Medriati, Rosane; Purwanto, Andik (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
The independent curriculum emphasizes developing critical thinking skills and solving scientific, analytical, and practical problems. Schools need to facilitate learning that enhances these skills, and teachers must create appropriate strategies. Interviews with physics teachers at SMAN 11 Kota Bengkulu reveal that the independent curriculum is implemented, but assessment data and daily exams show that 50-60% of grade XI students struggle with solving physics problems. Students tend to be passive, memorizing formulas without understanding the concepts deeply. This indicates a lack of critical thinking skills such as analyzing, synthesizing, solving problems, concluding, and evaluating material, especially in linear motion kinematics. Additionally, students’ interest in learning is low, and they find physics difficult. To address this, a STEM-based Problem Based Learning (PBL) model was applied. This study aims to determine the effect of STEM-based PBL on improving students’ critical thinking skills and the extent of improvement in linear motion kinematics. The study used a quasi-experiment with a non-equivalent control group design, with XI C as the control class and XI B as the experimental class.